RESEARCH ON VIBRATION SUPPRESSION PERFORMANCE OF BNES BASED ON MAGNETIZING CURRENT METHOD (MT) - SONG WeiZhi; ZHOU Hui; LIU ZhiEn; LI Bin; ZHU DeRong; CHEN ZhiYong (Jixie qiangdu)
A bistable-nonlinear energy sink（BNES） is designed to control the vibration of the main system in a wide frequency range. The spatial magnetic force of cantilever structure system is analyzed based on the magnetizing current theory, and the influences of magnetic spacing and cantilever length on stability point of BNES are studied. The dynamic equations of main system coupling BNES are established to study the stability of transient performance of BNES under different excitation intensities. The effect of magnetic spacing on the steady-state vibration reduction performance of the BNES is studied through the amplitude frequency characteristics, and the stability performance of the BNES with the change of excitation intensity at 0.5 times, 1 times and 1.5 times resonant excitation frequency is studied. The analysis results show that the proposed BNES has good transient and steady-state vibration reduction performance and good robustness.